2020
DOI: 10.3390/jrfm13120318
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Educational Technologies in CSR Perception of Tourism Education: The Comparative Analysis of E-Learning and M-Learning Tools as Moderators

Abstract: The aim of this study is to investigate the effect of educational technologies on the Corporate Social Responsibility (CSR) perception of tourism students and their intention to work in the tourism business industry. By improving education programs with an investment in educational technologies, both universities and firms are believed to benefit from growing CSR initiatives, as well as potential young talents for their future business activities. Four-dimensional (economic, legal, ethical and philanthropic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…For example, investors such as the World Bank and Coursera are aiming at MOOCs as a broader program to help students developing market-related IT capabilities. Therefore, these initiatives have significant corporate and governmental funding (John Thomas and Khalil, 2020).…”
Section: Literature Review 21 Higher Education and Employabilitymentioning
confidence: 99%
“…For example, investors such as the World Bank and Coursera are aiming at MOOCs as a broader program to help students developing market-related IT capabilities. Therefore, these initiatives have significant corporate and governmental funding (John Thomas and Khalil, 2020).…”
Section: Literature Review 21 Higher Education and Employabilitymentioning
confidence: 99%
“…Our aim is to address the research gap identified in the field of mobile learning (m-learning) focused on economic education at the high school level. Limited studies have been conducted on this topic, with most of the existing research primarily concentrated on higher education [3,[42][43][44]. It is crucial to note that students studying economics will play a pivotal role in the future digital economy.…”
Section: Introductionmentioning
confidence: 99%
“…Yet another research investigated the effect of educational technologies on the perception of tourism students and their intention to work thereafter. Different M-learning and Elearning platforms were compared to assure the most effective platform for CSR education among the students, which eventually found that e-learning tools are rather more effective [13]. Hence, virtual reality, chatbots, and immersive apps have added more functionality and greater potential for learning.…”
Section: Introductionmentioning
confidence: 99%